Nitrogenases in Oxygen Minimum Zone Waters - Reeder, Christian Furbo; Löscher, Carolin Regina (Frontiers in Marine Science, 2022)
Biological dinitrogen (N2) fixation is the pathway making the large pool of atmospheric N2 available to marine life. Besides direct rate measurements, a common approach to explore the potential for N2 fixation in the ocean is a screening based targeting the key functional marker gene nifH, coding for a subunit of the nitrogenase reductase. As novel sequencing techniques improved, our understanding of the diversity of marine N2 fixers grew exponentially. However, one aspect of N2 fixation in the ocean is often underexplored, which are the two alternative types of N2 fixation. Altogether there are three isoenzymes, the most common Mo-Fe nitrogenase Nif, the Fe-Fe nitrogenase Anf, and the V-Fe nitrogenase Vnf, which differ regarding their genetic organization, as well as their metal co-enzymes. While Mo is only available in the presence of at least traces of oxygen (O2), V and Fe are available if O2 is absent. Therefore, low O2 and anoxic ocean environments could be an ideal place to explore the diversity of the different isotypes of the nitrogenase. Most phylogenetic studies, however, were only based on the functional marker gene nifH, encoding for a subunit of the Nif nitrogenase, and thus limited in representing the diversity of alternative nitrogenases. Here, we screened metagenomes and -transcriptomes from O2 minimum zones off Peru, from the Bay of Bengal OMZ, and the anoxic Saanich Inlet to explore the diversity of genes involved in N2 fixation. We identified genes related to all three nitrogenases, and a generally increased diversity as compared to our previous nifH based on studies from OMZ waters. While we could not confirm gene expression of alternative nitrogenases from our transcriptomes, we detected additional diazotrophs involved in N2 fixation harboring alternative nitrogenases. We suggest that alternative nitrogenases may not be used under conditions present in those waters, however, depending on trace metal availability they may become active under future ocean deoxygenation.